An exploration of fairness in international law through the Blue Nile and GERD. Issue 4 (6th June 2016) - Yihdego, Zeray; Rieu-Clarke, Alistair
ABSTRACT: The principle of fairness operates alongside lofty principles of international law, such as equity and justice. However, these concepts often face criticism for being too vague to shed any meaningful light on the practical interpretation and implementation of international law within specific fields. By analysing the cooperation between Egypt, Ethiopia and Sudan on the Blue Nile, this paper seeks to address such criticism. It suggests that the concept of fairness does have value as a framework for analysing both commitment and compliance in international law; and that exploring specific contexts, such as legal developments related to the Blue Nile, helps give it further meaning.